Size Dependent Policies, Informality and Misallocation - Dabla-Norris, Era (IMF Working Papers; Working Paper ;, 2018)
We examine the effect of size-dependent policies in developing economies by focusing on a set of regulations that are applicable to firms with 20 or more formal employees in Peru. Firms can adjust to the regulations by (a) reducing their size, (b) shifting employment composition, or (c) splitting into subunits that fall below the regulatory threshold. We show that these actions are consistent with observed discontinuities in the distributions of firm size and employment composition. We extend the framework proposed by Garicano and others (2016) to model and estimate the Peruvian economy and perform counterfactual exercises. Size-dependent regulations are costly for the economy, especially in the presence of labor market rigidities, and lead to lower aggregate wages, profits, and output. We also find that access to informal labor does not mitigate the economic impact of the size-dependent regulations, as the increase in informal employment is largely offset by a decline in formal employment.